2021
DOI: 10.25083/rbl/26.2/2499.2510
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of some traditional medicinal plants: phytochemical profile, antibacterial and antioxidant potentials

Abstract: Bioassays provide an authentication of the traditional knowledge of medicinal plants. Antibacterial, antioxidant and phenolic content of nine medicinal plants (Achillea millefolium, Prunella vulgaris, P. laciniata, Lythrum salicaria, Epilobium angustifolium, E. hirsutum, Pedicularis comosa, Agrimonia eupatoria and Verbena officinalis) were investigated in connection with folkloric usages. Aerial parts of nine plant species were extracted with water and methanol (MeOH). Disc diffusion method was performed to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 0 publications
0
32
1
1
Order By: Relevance
“…Moreover, previous studies indicated the presence of other phenolic constituents, mainly apigenin, kaempferol, and quercetin derivatives, as well as catechin and oligomeric proantocyanidins [ 25 ]. In contrast to our study, rosmarinic acid has previously been found to be the dominant compound in the methanolic extract of A. eupatoria L. In addition to rosmarinic acid, rutin, apigenin, kaempferol, and quercetin (in order of decreasing quantity) were also determined [ 30 ]. In our aqueous extract, rosmarinic acid and quercetin were not detected, and the HPLC chromatogram revealed only small amounts of gallic and cinnamic acid.…”
Section: Resultscontrasting
confidence: 99%
“…Moreover, previous studies indicated the presence of other phenolic constituents, mainly apigenin, kaempferol, and quercetin derivatives, as well as catechin and oligomeric proantocyanidins [ 25 ]. In contrast to our study, rosmarinic acid has previously been found to be the dominant compound in the methanolic extract of A. eupatoria L. In addition to rosmarinic acid, rutin, apigenin, kaempferol, and quercetin (in order of decreasing quantity) were also determined [ 30 ]. In our aqueous extract, rosmarinic acid and quercetin were not detected, and the HPLC chromatogram revealed only small amounts of gallic and cinnamic acid.…”
Section: Resultscontrasting
confidence: 99%
“…In yarrow, the following phenolic acids and their derivatives were detected: gallic, caffeic acids, chlorogenic acid derivative, protocatechuic acid hexoside. Among flavonoids, quercetin, quercetin rutinoside, quercetin glucoside, luteolin, luteolin glucoside, kaempferol, myricetin, apigenin, apigenin glucoside were found [ 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ayrıca 200 μg/mL konsantrasyonda DPPH radikalini %96,2 oranında inhibe ettiği belirtilmiştir. 25 Iancu 2021 yılındaki araştırmasında, bitkinin toprak üstü kısımlarının su ekstresinin toplam fenol içeriğini %16,3 bulmuş, 1 mg/mL konsantrasyonda DPPH radikalini %92 oranında inhibe ettiğini belirtmiştir. 26 Bir başka çalışmada ise yine aynı bitkinin toprak üstü kısımlarının %80 metanol ekstresinin toplam fenol içeriğinin 331 µg GAE/mg; toplam flavonoit içeriğinin ise 5,8 μg kersetin eşdeğeri/mg olduğu hesaplanmıştır.…”
Section: üReaz Inhibe Edici Aktivite Tayiniunclassified